Perbedaan Perilaku Konsumtif Pada Perempuan Berkerja Dan Perempuan Tidak Berkerja - Putri, Yunia Purnamasari; Supriyati, Supriyati; Purnama, Rahmad (Universitas Islam Negeri Raden Intan Lampung, 2021)
Consumptive behavior is currently found in various kinds of social status. Both from the businessmen, traders, civil servants, students, men and women. Many women who work or not work always shop. It is possible that women who do not work also have consumptive behavior because in today's sophisticated era, access to purchases is easy. When they are happy or sad, they prefer to shop. But it can make them have the habit of shopaholic aka crazy shopping. The purpose of this comparative research is to reveal or find out the differences in consumptive behavior between working women and non-working women. Researchers used quantitative research methods with purposive sampling technique. The population in this study were women who worked and did not work at Dusun Calling 1 Desa Serbajadi 1. After doing the try out, the researcher did the actual research. The subjects in this study were Serbajadi 2 Hamlet with 80 subjects consisting of 40 working women and 40 unemployed women. Based on the results of data analysis in this study and reinforced by the theoretical basis that has been described, it can be concluded that